Manfaat Merek Dagang Terdaftar Bagi Pelaku UMKM di Kota Surakarta: Studi Kasus Perlindungan HKI - Patrica Ingarasi; Nany Pudianti Suwigno (CV. Social Politic Genius (SIGn), 2022)
This research aims to examine and analyze the benefits obtained by MSME actors in Surakarta after registering their trademarks. This research uses the empirical research method. The primary data were collected using direct interviews. The data obtained in this research were then analyzed qualitatively to analyze problems and answer study purposes. The results show that the IPR has provided legal certainty and protection for the Owner. Apart from getting legal protection, the rights Owner of the trademark also gets material and immaterial benefits. In this case, the rights Owner of the Mal Mel trademark feels the immaterial benefits. Furthermore, the rights Owner of the Mal Mel trademark prefers to give a direct warning if she finds a social media account plagiarizing his trademark rather than through positive legal procedures. At the same time, the rights Owner of the Mal Mel trademark does not think of making a profit by earning and receiving compensation from plagiarists. Therefore, it is recommended for every business actor, especially those with large and developing scales, to register their trademarks. In addition, MSME actors can also register the trademark to DGIP using the collective system. On the other hand, it is also recommended for the Government increase public understanding and trust in solving problems through positive legal procedures, even though the crime of IPR plagiarism is included in the category of constituted complaint delict.